The Media as a Window on the Past? The Impact of Television and Newspaper Consumption on Knowledge of the Democratic Transition in Portugal - Santana-Pereira, José (2016)
This study seeks to expand our understanding of how the media increase the level of political information, by focusing on an understudied yet important learning outcome: knowledge of the political past. The article explores the factors underlying variation in the recognition of the leading actors in the transitional process in Portugal. The results show that television news and newspaper exposure foster recognition of these actors, but that media use interacts with personal experience of the transition (stronger effects among younger cohorts) and party identification (stronger impact on those who do not feel close to a political party).